An Investigation of Descending Pain Modulation in Women With Provoked Vestibulodynia (PVD): Alterations of Spinal Cord and Brainstem Connectivity - Yessick, Lindsey R.; Pukall, Caroline F.; Ioachim, Gabriela; Chamberlain, Susan M.; Stroman, Patrick W. (Frontiers in Pain Research, 2021)
The most common subtype of vulvodynia (idiopathic chronic vulvar pain) is provoked vestibulodynia (PVD). Previous imaging studies have shown that women with vulvodynia exhibit increased neural activity in pain-related brain regions (e.g., the secondary somatosensory cortex, insula, dorsal midcingulate, posterior cingulate, and thalamus). However, despite the recognized role of the spinal cord/brainstem in pain modulation, no previous neuroimaging studies of vulvodynia have examined the spinal cord/brainstem. Sixteen women with PVD and sixteen matched Control women underwent a spinal cord/brainstem functional magnetic resonance imaging (fMRI) session consisting of 5 runs with no painful stimuli (No Pain), interleaved randomly with 5 runs with calibrated, moderately painful heat stimulation (Pain). Functional connectivity was also assessed in periods before, during, and after, pain stimulation to investigate dynamic variations in pain processing throughout the stimulation paradigm. Functional connectivity in the brainstem and spinal cord for each group was examined using structural equation modeling (SEM) for both Pain and No Pain conditions. Significant connectivity differences during stimulation were identified between PVD and Control groups within pain modulatory regions. Comparisons of Pain and No Pain conditions identified a larger number of connections in the control group than in the PVD group, both before and during stimulation. The results suggest that women with PVD exhibit altered pain processing and indicate an insufficient response of the pain modulation system. This study is the first to examine the spinal cord/brainstem functional connectivity in women with PVD, and it demonstrates altered connectivity related to pain modulation in the spinal cord/brainstem.